2022
DOI: 10.3389/fcvm.2021.805735
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Cardio-Oncology: Exercise as a Potential Therapeutic Modality in the Management of Anthracycline-Induced Cardiotoxicity

Abstract: Anthracyclines are one of the most effective chemotherapy agents and have revolutionized cancer therapy. However, anthracyclines can induce cardiac injuries through ‘multiple-hits', a series of cardiovascular insults coupled with lifestyle risk factors, which increase the risk of developing short- and long-term cardiac dysfunction and cardiovascular disease that potentially lead to premature mortality following cancer remission. Therefore, the management of anthracycline-induced cardiotoxicity is a serious unm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 144 publications
1
13
0
Order By: Relevance
“…A state-ofthe-art review recently highlighted the importance of exercise in childhood cancer survivors and its key role in preventing chemotherapy-related cardiotoxicity (15). Indeed, chemotherapy-related cardiotoxicity leads to cardiac dysfunctions (e.g., decline in left ventricular ejection fraction), because of mitochondrial biogenesis impairment (36), whereas exercise stimulates mitochondrial biogenesis (37). Moreover, observational studies have reported that exercise in childhood cancer survivors improves left ventricular ejection fraction (38, 39) and markers of cardiovascular health (33,40).…”
Section: Healthy Lifestyle In Childhood Cancer Survivorsmentioning
confidence: 99%
“…A state-ofthe-art review recently highlighted the importance of exercise in childhood cancer survivors and its key role in preventing chemotherapy-related cardiotoxicity (15). Indeed, chemotherapy-related cardiotoxicity leads to cardiac dysfunctions (e.g., decline in left ventricular ejection fraction), because of mitochondrial biogenesis impairment (36), whereas exercise stimulates mitochondrial biogenesis (37). Moreover, observational studies have reported that exercise in childhood cancer survivors improves left ventricular ejection fraction (38, 39) and markers of cardiovascular health (33,40).…”
Section: Healthy Lifestyle In Childhood Cancer Survivorsmentioning
confidence: 99%
“…Cancer survivors have been found to have a several-fold increased incidence of cardiovascular risk factors (9), and this condition causes a higher risk of premature morbidity and mortality. To mitigate the risk, it has recently been strongly recommended to integrate a model of comprehensive cardiac rehabilitation, also called Cardio-Oncology REhabilitation (CORE), for the population of cancer patients and survivors (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, CTRCD prevention methods focus on minimizing radiation exposure and cumulative anthracycline dose. Strategies also include liposomal encapsulated anthracyclines delivery [ 10 ] and improvements in radiation therapy that exhibit reduced cardiotoxic properties while maintaining high antineoplastic effects [ 11 ]. Unfortunately, these strategies do not apply to all cases [ 11 ] and do not fully mitigate CTRCD risk [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies also include liposomal encapsulated anthracyclines delivery [ 10 ] and improvements in radiation therapy that exhibit reduced cardiotoxic properties while maintaining high antineoplastic effects [ 11 ]. Unfortunately, these strategies do not apply to all cases [ 11 ] and do not fully mitigate CTRCD risk [ 10 ]. Dexrazoxane is the only widely used pharmaceutical for preventing anthracycline-induced CTRCD [ 3 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation